The Influence of Fraud Hexagon and Audit Committee Effectiveness on Fraudulent Financial Reporting - Esliani, Riski; Irwansyah, Irwansyah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This study's primary goal is to present empirical data on the components of the fraud hexagon and the audit committee's efficacy in identifying signs of false financial reporting. The data for this study come from financial statements and annual reports of mining companies listed on the IDX for 2019-2023. The purposive sampling method is used to collect research samples. The analysis was carried out using logistic regression analysis with the help of Eviews 12 software. The results of this study indicate that financial targets and state-owned enterprises affect fraudulent financial reporting. At the same time, CEO education, the nature of the industry, auditor change, frequent CEO's picture, and audit committee effectiveness have no effect. The results of this study indicate that financial targets representing stimulus and state-owned enterprises representing collusion affect fraudulent financial reporting while CEO education, nature of the industry, auditor change, frequent CEO's picture, and audit committee effectiveness have no effect. Hence, it can be concluded that the fraud hexagon elements that have an effect are stimulus and collusion while other elements have no effect. Audit committee effectiveness does not affect fraudulent financial reporting. However, this research is limited to the mining sector, so it is recommended to expand the sample coverage in other sectors to get more comprehensive and representative results.